2016
DOI: 10.1186/s13287-016-0304-5
|View full text |Cite
|
Sign up to set email alerts
|

Restrained Th17 response and myeloid cell infiltration into the central nervous system by human decidua-derived mesenchymal stem cells during experimental autoimmune encephalomyelitis

Abstract: BackgroundMultiple sclerosis is a widespread inflammatory demyelinating disease. Several immunomodulatory therapies are available, including interferon-β, glatiramer acetate, natalizumab, fingolimod, and mitoxantrone. Although useful to delay disease progression, they do not provide a definitive cure and are associated with some undesirable side-effects. Accordingly, the search for new therapeutic methods constitutes an active investigation field. The use of mesenchymal stem cells (MSCs) to modify the disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 85 publications
(104 reference statements)
3
45
0
1
Order By: Relevance
“…Using hBM‐MSCs, Bai et al showed a decrease in leukocyte infiltration into the CNS and enhanced a Th2 cytokine profile, but also enhanced oligodendrogenesis, suggesting that hBM‐MSCs affect immunomodulation but also enhanced neuronal repair . Similar results showing a Th2 cytokine shift and enhanced oligodendrogenesis were reported using hA‐MSCs and using human decidua‐derived MSCs (hD‐MSCs) . hA‐MSCs were also shown to express the immunosuppressive gene human leukocyte antigen G (HLA‐G) and to induce the secretion of the anti‐inflammatory protein TNF‐α‐stimulated gene/protein 6 following culture with inflammatory cytokines .…”
Section: Immunomodulation and Neuroinflammationmentioning
confidence: 67%
“…Using hBM‐MSCs, Bai et al showed a decrease in leukocyte infiltration into the CNS and enhanced a Th2 cytokine profile, but also enhanced oligodendrogenesis, suggesting that hBM‐MSCs affect immunomodulation but also enhanced neuronal repair . Similar results showing a Th2 cytokine shift and enhanced oligodendrogenesis were reported using hA‐MSCs and using human decidua‐derived MSCs (hD‐MSCs) . hA‐MSCs were also shown to express the immunosuppressive gene human leukocyte antigen G (HLA‐G) and to induce the secretion of the anti‐inflammatory protein TNF‐α‐stimulated gene/protein 6 following culture with inflammatory cytokines .…”
Section: Immunomodulation and Neuroinflammationmentioning
confidence: 67%
“…Delay of the disease onset and reduction of the disability score Bravo et al (2016) in a Chinese population . In detail, on day 0, eight enrolled patients received an intravenous injection of 2 × 10 7 hUC-MSCs followed by an intrathecal injection at the same dose.…”
Section: Fetal Annexes-derived Mscsmentioning
confidence: 99%
“…In a recent study conducted in 2016, Bravo et al (2016) used the EAE model in order to evaluate the therapeutic effects of human decidua-derived MSCs (DD-MSCs). DD-MSCs are a cell population obtained from placental extraembryonic membranes and with a proliferation rate and capacity to differentiation higher than BM-MSCs.…”
Section: Fetal Annexes-derived Mscsmentioning
confidence: 99%
“…A potential alternative to neural precursor cells is mesenchymal stem cells (MSC). Recently, the actions exerted by adipose-derived mesenchymal stromal cells, [10][11][12][13][14] placenta-derived mesenchymal stem cells, 15,16 Wharton's jelly mesenchymal stem cells, 17 human decidua-derived mesenchymal stem cells 18 and human umbilical cord blood mesenchymal stromal cells 19 have been reported in experimental autoimmune encephalomyelitis (EAE) animal models.…”
Section: Introductionmentioning
confidence: 99%
“…These cells could be ideal candidates for application in human diseases, since they offer significant practical advantages: they are obtained from different adult tissues and can readily be cultured and expanded; they are multipotent and self-renewing. They have the capacity to differentiate into mesodermal-derived 20 or into neural-like and glial-like cells 21 ; they have been shown to have immunoregulatory properties 10,[12][13][14]17,18,22,23 ; they secrete factors that may stimulate endogenous neural stem cells in the CNS 24,25 ; they can be safely injected autologously without the need for immunosuppression 26 ; they decrease the number of infiltrating inflammatory cells, preserving axons and ameliorating demyelination, 15,19,27,28 ameliorate neuroinflammation 11,29 and exert a neurotrophic action. 16 All these features make MSC suitable for therapy in autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%